Dystocia due to hydrothorax monster calf in a Mehsani buffalo - SIDDIQUEE, G M; FARUQUE, S; PANDEY, R K (The Indian Journal of Animal Reproduction, 2023)
A case of dystocia due to hydrothorax monster calf in a buffalo has been reported. The dystocia was relieved by performing cesarean operation and puncturing the thoracic cavity to reduce the calf size and provide access for extraction.